Detection of Antichlamydial Antibody in Patients With Ectopic Pregnancy and Normal Pregnancy - Jamal Murad, Srwa (Kurdistan Journal of Applied Research, 2020)
Aim of the current research is to assess the Chlamydia Trachomatis infection role in the development of early pregnancy complication including ectopic pregnancy and miscarriage in Sulaimanyia Maternity Teaching Hospital. It is a comparative study conducted in Gynecology Clinic and Emergency department of Sulaimanyia Maternity Teaching Hospital during the period from 1st of September 2018 to 31st of March 2019. The study groups included of 70 pregnant women; the first group included 35 ectopic pregnant women and the second group included 35 normal pregnant women that both groups had been selected randomly. Pregnant women with history of ectopic pregnancies, women used intrauterine device, in vitro fertilization, assisted reproduction and history of pelvic surgery. Blood sample (2 ml venous blood) collected to test for antibodies level for Chlamydia Trachomatis by Alegria test system for both studied groups and patients with ectopic pregnancy detected by beta human chorionic gonadotropin and ultrasound scanning. The collected data analyzed by SPSS program and for compare between means of two variables independent sample t-test was used while for comparison of categorical variables Chi square test was used with considering ? 0.05 P-value as significant level. The results shows that the mean age of normal pregnancy were (28.3±4.6) group compared with mean age ectopic pregnancy (29.5±4.9) group. The mean IgG (6.3±5.1) of patients with ectopic pregnancy was found to be significantly higher than mean IgG (2.8±1.1) for normal pregnant patients (P-value 0.01) and IgM mean (4.5±2.4) of patients with ectopic pregnancy was significantly higher than mean IgM (1.6±1.2) for normal pregnant patients with P-value 0.01. In conclusion, infection of Chlamydia Trachomatis has a significant relationship with the development of ectopic pregnancy therefor screening and treatment of Chlamydia infection may reduce ectopic pregnancy rate with low cost